Carbon Dot‐Based Hydrogels: Preparations, Properties, and Applications (Small 17/2023). Issue 17 (27th April 2023) - Wang, Yijie; Lv, Tingjie; Yin, Keyang; Feng, Ning; Sun, Xiaofeng; Zhou, Jin; Li, Hongguang
Abstract : Carbon Dot‐Based Hydrogels The features of article number 2207048 by Xiaofeng Sun, Jin Zhou, Hongguang Li, and co‐workers include i) preparations of carbon dot (CD)‐based hydrogels, including CDs/polymers, CDs/low molecular weight gelators, CDs/graphene oxide, CDs/metal ions and derivatives of CD‐based hydrogels, ii) properties of CD‐based hydrogels, such as fluorescence, mechanical strength enhancement, self‐healing, and stimulus response, iii) applications of CD‐based hydrogels in biomedicine, sensing, adsorption, energy storage and catalysis.